2020
DOI: 10.1016/j.jpsychores.2020.110221
|View full text |Cite
|
Sign up to set email alerts
|

Psychological status of healthcare workers during the civil war and COVID-19 pandemic: A cross-sectional study

Abstract: Objective Healthcare workers, particularly those working in departments that provide care for patients with coronavirus disease 2019 (COVID-19), are at a higher risk of this contagious disease than those who work in other departments. The aim of this study was to assess the psychological status of healthcare workers during the COVID-19 outbreak, which has compounded Libya's existing civil war-related problems. Methods A multi-center cross-sectional survey on depressive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
85
1
17

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(106 citation statements)
references
References 46 publications
3
85
1
17
Order By: Relevance
“…In a study during the H1N1 outbreak, hospital staff who were in their 20's had greater anxiety about becoming infected than did older staff ( 103 ). During COVID-19, HCW who were younger were more likely to experience higher levels of post-traumatic stress symptoms, depression, anxiety, and acute stress compared to older HCW ( 23 , 26 28 , 30 , 32 , 42 , 49 , 54 , 55 , 57 , 61 , 65 , 71 , 75 , 78 , 89 , 90 , 117 , 118 , 121 , 123 , 127 , 131 , 149 , 153 , 154 ). In contrast, eight studies conducted during COVID found that HCW who were older were at greater risk of experiencing higher levels of psychological distress ( 40 , 66 , 86 , 95 , 102 , 114 , 122 , 132 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study during the H1N1 outbreak, hospital staff who were in their 20's had greater anxiety about becoming infected than did older staff ( 103 ). During COVID-19, HCW who were younger were more likely to experience higher levels of post-traumatic stress symptoms, depression, anxiety, and acute stress compared to older HCW ( 23 , 26 28 , 30 , 32 , 42 , 49 , 54 , 55 , 57 , 61 , 65 , 71 , 75 , 78 , 89 , 90 , 117 , 118 , 121 , 123 , 127 , 131 , 149 , 153 , 154 ). In contrast, eight studies conducted during COVID found that HCW who were older were at greater risk of experiencing higher levels of psychological distress ( 40 , 66 , 86 , 95 , 102 , 114 , 122 , 132 ).…”
Section: Resultsmentioning
confidence: 99%
“…In HCW during the SARS outbreak, those with <10 years of experience reported higher levels of psychological distress, but not burnout or post-traumatic stress, 13–26 months after the outbreak ( 14 ). HCW who had less clinical experience were also more likely to experience stress during the COVID-19 outbreak ( 23 , 28 , 55 , 65 , 69 , 154 ). Years of clinical experience was not associated with PTSD symptoms, acute stress or anxiety, depression, mental health status, or burnout in 21 other studies ( Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, the civil war has caused displacement among physicians; 32.5% of physicians have left their homes due to the conflict. This situation places more pressure on these healthcare professionals, who fear their homes being destroyed or taken over by militias (51). Finally, they have concerns regarding the COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…With regard to our second hypothesis, we were able to prove that greater exhaustion, greater family strain, and reduced feelings of protection impact on levels of anxiety among physicians. Other research from the developed world [29], developing countries [30], and Pakistan itself [31] corroborate that physicians are suffering from anxiety during the pandemic. Higher workload is a crisis these days across the world due to staff shortages, leading to long and stressful duties for critical patients [32].…”
Section: Discussionmentioning
confidence: 81%